2015
DOI: 10.1097/sap.0000000000000157
|View full text |Cite
|
Sign up to set email alerts
|

Decellularization of a Fasciocutaneous Flap for Use as a Perfusable Scaffold

Abstract: A combination of perfusion and agitation for 24 hours or longer effectively decellularized the fasciocutaneous portion of composite tissue flaps and removed DNA content from the flap in our rat model with well-preserved vascular structure. This combined technique was superior to agitation alone. However, closed-loop circulation could not be preserved after decellularization with perfusion and/or agitation methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Thus, skin/adipose tissue flap engineering has tremendous impact in the field of reconstructive surgery. Studies have shown that a completely decellularized skin flap matrix retains its vascular structure intact [13, 14]. However, details about the characterization of the acellular skin flap matrix are lacking, and the interaction between the cells and scaffold matrix during the remodeling process has not yet been investigated in vitro or in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, skin/adipose tissue flap engineering has tremendous impact in the field of reconstructive surgery. Studies have shown that a completely decellularized skin flap matrix retains its vascular structure intact [13, 14]. However, details about the characterization of the acellular skin flap matrix are lacking, and the interaction between the cells and scaffold matrix during the remodeling process has not yet been investigated in vitro or in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Perfusion decellularization and recellularization has shown promising preclinical results for transplantation of organs (e.g., heart, lung, kidney, and liver) and complex tissues (e.g., limbs, face, ears, fascio‐cutaneous flaps) in small and large animal models . Henderson et al and Qu et al have described effective decellularization of a small fascio‐cutaneous flap based on SIE vessels in rats . Duisit et al decellularized hemi‐facial grafts in rats and decellularized/recellularized both human facial grafts and porcine ears .…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22] Henderson et al and Qu et al have described effective decellularization of a small fascio-cutaneous flap based on SIE vessels in rats. 28,29 Duisit et al decellularized hemi-facial grafts in rats and decellularized/recellularized both human facial grafts and porcine ears. 20,21,30 Recently, Jank et al successfully decellularized/recellularized entire limbs in rats and primates and a complex fascio-cutaneous flap in swine.…”
Section: Discussionmentioning
confidence: 99%
“…A skin flap consists of healthy skin and fat or skin, fat, and muscle. 46 This optimized protocol has been successfully reported in miniature swine model. Hence, the decellularization of skin flaps is essential.…”
Section: Decellularized Skin Flapsmentioning
confidence: 91%
“…Dvir and coworkers began decellularization procedures with freeze/thaw cycles, demonstrating that freezing was necessary to completely remove nuclei and DNA 31,32 ; however, freeze/thaw cycles would disrupt the microstructure of ECM. 46 Despite remarkable differences in decellularization techniques, all protocols have shown complete removal of nuclei and reduction in DNA content as well as preservation of ECM microstructure together with the major components of the ECM such as collagen, elastin, laminin, and glycosaminoglycans. 33,34,36 During skin flaps decellularization, agitation and perfusion decellularization are demonstrated to be effective, while perfusion treatment could retain the vascular structure well, compare to agitation.…”
Section: Protocols For Decellularizationmentioning
confidence: 99%